Analysis of Factors Influence Micro Enterprises Online Purchase Intention on Social Media Agency Services with Mediation of Attitude towards Social Media in Kabupaten Tangerang During Covid-19 Pandemic - Anastasia Joveta; Y. Budi Susanto; Krist Ade Sudiyono (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
Begin with the Covid-19 as digital accelerator brings people to access social media daily, social media agency come as a solution to help micro business to survive on the pandemic era. Therefore, the social media agency is facing a hypercompetitive situation and need to know the factor of micro business having an intention to purchasing their services. Based on the findings, Subjective Norms (SN), Perceived Usefulness (PU), Perceived Behavioral Control (PBC), Cost (C), Attitude toward social media (ASM) significantly influence micro business owners online purchase intention. Therefore, Perceived Usefulness is significantly influenced online purchase intention using mediating variable. It describes that the highest influenced factor is Perceived Usefulness, which improve respondent online purchase intention, with or without any mediating variables. Also, it shows that attitude towards social media was not significantly influenced as a mediator. From the result, it can be suggested on the social media agency to focused more on how their services can bring an effort saving and enhance micro business in Kabupaten Tangerang through social media, especially on the post-pandemic situation. Its also recommended for the micro business owner to considered using social media agency for an effective workflow on activating social media for business.